Climatological seasonal changes of wind and rainfall in the Philippines - Matsumoto, Jun (Archīum Ateneo, 2020)
Climatological seasonal changes of rainfall and lower tropospheric circulation in and around the Philippines are analysed by utilizing the TRMM 3B42 to obtain the 5‐day mean rainfall and ERA‐Interim wind data for the period 1998–2013. In particular, climatological onset and withdrawal processes of the southwest (SW) and northeast (NE) monsoon are investigated. It is found that the onset of the SW monsoon occurs abruptly in mid‐May almost simultaneously over the Philippines except in the southern region. The start of the SW monsoon in the Philippines occurs earlier in the north than in the south. In addition, a climatological increase in rainfall on the west coast precedes the SW monsoon arrival by approximately two pentads, due to tropical cyclone influences in some years. After the SW monsoon onset, the monsoon trough is located over the southern Philippines. In mid‐June, the monsoon trough begins to deepen, and migrates northward to the central Philippines, and easterly winds intrude shortly to the northern Philippines. Then, the entire Philippines is covered by the summer monsoon westerly in early July, which is followed by the rainfall peak over the west coast region occurring in early August. The SW monsoon begins to retreat from the north in mid‐September, and fully retreats from the Philippines rather suddenly in late September. In general, the rainfall amount in the west coastal region remains high for approximately 2 months after this wind reversal, showing relatively larger post monsoon rainfall due mainly to tropical cyclone effects. During the NE monsoon season, the rainfall centre in the east coast is located in the northern and central region until mid‐December. Afterwards it is anchored in the southern region from late December to mid‐March, indicating the fully established NE monsoon season.